Exploring the functional role and neural correlates of K-complexes in isolated rapid eye movement sleep behavior disorder. (December 2021) - Galbiati, Andrea; Carli, Giulia; Fasiello, Elisabetta; Casoni, Francesca; Zucconi, Marco; De Gennaro, Luigi; Perani, Daniela; Ferini-Strambi, Luigi
Abstract: Underlying neural mechanisms and cognitive implications of non-Rapid Eye Movement (NREM) sleep in isolated Rapid Eye Movement (REM) sleep behavior disorder (iRBD) are not yet fully elucidated. This study aims to evaluate brain metabolic connectivity of the anterior default mode network (ADMN) underlying a waveform that is an hallmark of NREM sleep, namely K-complex (KC) and their implication for neuropsychological functioning in iRBD patients. Combining polysomnographic and multivariate molecular imaging (FDG-PET) approaches may provide crucial insights regarding KCs role in the prodromal stages of synucleinopathies. We applied a seed-based interregional correlation analysis on FDG-PET data. iRBD patients with cognitive decline displayed a reduced KC density (KCd) in comparison to patients without cognitive impairments. KCd showed a significant positive correlation with global cognitive functioning, specifically with visuo-spatial and executive performances, two cognitive domains known to be relevant in predicting conversion into neurodegenerative disorders. Increased KCd was associated with a more preserved ADMN connectivity. Our study underlines the importance of NREM sleep in prodromal stages of synucleinopathies, and future investigations might clarify its role in iRBD.